Penerapan PJBL untuk Meningkatkan Hasil Belajar Las SMAW Siswa SMK N 1 Guguak - Gusti Geriansyah; Jasman Jasman (TSAQOFAH, 2026)
The low learning outcomes of students in the SMAW Welding subject indicate the need to implement a learning model that can increase engagement, understanding, and practical skills in the vocational learning process. This study aims to improve the learning outcomes of eleventh-grade students in Welding, Fabrication, and Metal Engineering at SMK Negeri 1 Guguak through the implementation of the Project Based Learning model. This study used a Classroom Action Research (CAR) method conducted in three cycles, with the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 26 students. Data were collected through knowledge tests, observation, and project assessment of welding skills. The results of the study show that the students’ mean learning outcomes increased from 59.80 in the pre-cycle to 70.95 in Cycle I, 76.47 in Cycle II, and 80.10 in Cycle III. Classical mastery also increased from 30.76% in the pre-cycle to 38.46% in Cycle I, 76.92% in Cycle II, and 88.46% in Cycle III. The conclusion of the study affirms that the implementation of the Project Based Learning model can improve students’ learning outcomes in SMAW Welding, both in terms of knowledge and practical skills. The implications of this study indicate that project-based learning can serve as an effective alternative vocational learning model to strengthen active engagement, conceptual understanding, and practical skills among vocational high school students.